2021
DOI: 10.1108/jwam-02-2021-0020
|View full text |Cite
|
Sign up to set email alerts
|

The nexus of transactional leadership, knowledge sharing behavior and organizational creativity: empirical evidence from construction workers in Jakarta

Abstract: PurposeThis research aims to examine the role of knowledge sharing (KS) as mediation in the relationship between transactional leadership (TSL) and organizational creativity (OC) among construction workers in Jakarta.Design/methodology/approachThe population in this research was the construction workers working in Jakarta. The sample used in this research consisted of 210 respondents. The validity of the hypothesis model was analyzed using the structural equation modeling–partial least squares (SEM-PLS) approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 100 publications
(123 reference statements)
1
9
0
1
Order By: Relevance
“…The conclusion indicates that transactional leadership significantly positively affects knowledge sharing. Apart from that, Baskoro's (2022) research also shows the same results, where transactional leadership supports knowledge-sharing behavior in the construction sector in Indonesia. The previous study examines transformational leadership, such as Phung et al (2019), who studied the moderation effect of transformational leadership on personal and environmental factors on knowledge sharing among academic staff at public universities in Vietnam.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…The conclusion indicates that transactional leadership significantly positively affects knowledge sharing. Apart from that, Baskoro's (2022) research also shows the same results, where transactional leadership supports knowledge-sharing behavior in the construction sector in Indonesia. The previous study examines transformational leadership, such as Phung et al (2019), who studied the moderation effect of transformational leadership on personal and environmental factors on knowledge sharing among academic staff at public universities in Vietnam.…”
Section: Introductionsupporting
confidence: 61%
“…Transactional leadership focuses on reciprocity between leaders and employees. Transactional leaders must be able to explain goals, how to achieve these goals, and encourage employee commitment to creating new ideas by giving awards or recognition (Baskoro, 2022). Transformational leaders develop organizational collectivity by knowing the needs of employees to achieve organizational objectives (Bass, 1985).…”
Section: Leadershipmentioning
confidence: 99%
“…The foundation of belief is the conditional rewards presented by leaders to their subordinates. It has also been found that there are many optimistic associations between leadership style of transactional and employee participation of employees (Baskoro, 2021). All leaders want to change the current state of things but use different methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, creativity to find new solutions beyond seemingly impossible situations is a foundational idea (Sońta, 2022), but needs forms of leadership which embrace collective societal and planetary health and which usurps economic gain (Dwi Baskoro, 2022). This highlights the importance of a previous JWAM special issue which demonstrated practical case examples of how applied methodologies can deliver novel and creative solutions (Scott et al , 2020).…”
mentioning
confidence: 99%
“…To facilitate deep change, onboarding (Jeske and Olson, 2022) and coaching are critical and provide a wide range of positive contributions to transitions (Wang et al, 2022). Duringand importantly beyondinitial work socialisation, empathy is also critical to change (Lambert et al, 2022) especially for the different circumstances people experience in their life (Ochrach et al, 2022).Finally, creativity to find new solutions beyond seemingly impossible situations is a foundational idea (So nta, 2022), but needs forms of leadership which embrace collective societal and planetary health and which usurps economic gain (Dwi Baskoro, 2022). This highlights the importance of a previous JWAM special issue which demonstrated practical case examples of how applied methodologies can deliver novel and creative solutions (Scott et al, 2020).In sum, in times where peace is challenged, action (through applied methodologies), empathy and creativity are themes which remain highly relevant.…”
mentioning
confidence: 99%